Prevalence and Determinants of Pain in the Ipsilateral Upper Limb of Stroke Patients. Issue 3 (December 2014) - Kwon, Yong Hyun; Kwon, Jung Won; Lee, Na Kyung; Kang, Kyung Woo; Son, Sung Min
This study investigated the prevalence of pain in the ipsilateral upper-limb in stroke patients. 229 stroke patients (133 men, 96 women; M age = 59.0 yr., SD = 12.4) were assessed with the Pain Behaviors Scales and their motor weakness was measured with the Motricity Index. Results indicated that over 27% of patients experienced pain in at least one joint of the ipsilateral upper limb. Shoulder pain was the most common. Further analysis indicated that the occurrence of pain in the ipsilateral upper limb was higher among women, among patients who used a cane, and among patients with a greater weakness of the affected lower limb.